Assessing benefit in trials: Are we making progress in assessing progression in cancer clinical trials?. Issue 11 (21st October 2014) - Dancey, Janet E.
<x xml:space="preserve">Abstract</x> Intermediate endpoints that better capture the benefits of treatment and patient outcomes will facilitate trial conduct and ultimately treatment decisions for individual patients. Whether the current crop of newer endpoints will improve trial conduct and the interpretation of outcomes will require further evaluation.